KAJIAN STRUKTURAL DAN KONFLIK SOSIAL WAYANG ORANG BALAI SIGALA-GALA DAN RELEVANSINYA SEBAGAI BAHAN AJAR BAHASA JAWA PEMBENTUK SIKAP SOSIAL SISWA SMA - Dewi, Kartika Rahmat Sari; Suhita, Raheni; Waluyo, Budi (Universitas Sebelas Maret, 2017)
This research aimed to study structural element and social conflicts existing in Wayang Orang Balai Sigala-gala video and to find out whether or not it was relevance to be used as the teaching materials of Javanese language learning in the Senior High School. This study employed a descriptive qualitative approach with content analysis type of research by exploring structural elements and social conflicts in Wayang Orang Balai Sigala-gala and its relevance to be learning media. The information source used included reference book, video, informant as informant of interview. Techniques of collecting data used were Library Research as well as in-depth interview with data validation test using data source triangulation in which the author incorporated data obtained from interview of informant and the data obtained from reference study ad content analysis on the research object. The result of the research showed that Wayang Orang Balai Sigala-gala had complete structural elements, just like the constructive element existing in prose genre generally. The social conflict study conducted indicated that Wayang Orang Balai Sigala-gala had social conflict constituting the reflection in current social condition on society to be analyzed easily by the studied in the Senior High Schools. The consistency of conflict existing in Wayang Orang Balai Sigala-gala with the social condition made this video relevant to be a teaching materials into Javanese Language learning. Considering the result of research, it could be concluded that Wayang Orang Balai Sigala-gala was relevant to be teaching materials to Javanese Language Learning in the Senior High Schools.